2021
DOI: 10.1021/acs.iecr.1c03651
|View full text |Cite
|
Sign up to set email alerts
|

New Liquid Holdup Models in Both Preloading and Flooding Regions and a Flood Velocity Model to Identify Flooding for Sheet Metal Structured Packings

Abstract: Sheet metal structured packings are often employed in contacting columns because of their low pressure drops, high capacities, and high efficiencies. The liquid holdup on the packing sheets affects these attributes. Several researchers have developed various theoretical and empirical models for liquid holdup predictions. However, the majority of these models rely on packing-specific constants and detailed packing dimensions for model predictions. Such information is not readily available for many structured pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…It is evident that an increase in viscosity corresponds to an increase in liquid holdup, with higher viscosity exerting a more pronounced effect. An elevated viscosity imposes greater resistance on liquid flow, impeding flow at lower rates within the packing 23 . Additionally, Figure 3 highlights that the 24 cp liquid exhibits an earlier flooding point than the 1 and 12 cp liquids, indicating that a higher viscosity reduces the operational range of the packing column.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is evident that an increase in viscosity corresponds to an increase in liquid holdup, with higher viscosity exerting a more pronounced effect. An elevated viscosity imposes greater resistance on liquid flow, impeding flow at lower rates within the packing 23 . Additionally, Figure 3 highlights that the 24 cp liquid exhibits an earlier flooding point than the 1 and 12 cp liquids, indicating that a higher viscosity reduces the operational range of the packing column.…”
Section: Resultsmentioning
confidence: 99%
“…These experimental results and models have been widely applied in developing packings, designing columns, and simulating processes (i.e., Aspen, Fluent, and computational fluid dynamic). However, several research results have indicated that model‐predicted values may exhibit notable deviations from actual observations 15–17 . For instance, the SRP model yields inaccurate predictions for liquid holdup in Sulzer Mellapak packings, with an average deviation of 30.7%, leading to substantial discrepancies in evaluating packing performance, designing columns, and simulating processes 15 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations